Pogostost rentgenskih sprememb in nekaterih kliničnih kazalcev pri akutni pljučni emboliji - povezava s stopnjo pljučne arterijske obstrukcije - Požek, Igor (Zdravniški vestnik, 2005)
Background. The aim of the study was to find out if chest x-ray abnormalities and some clinical signs and findings in patients with acute pulmonary embolism(PE) correlate with the degree of pulmonary arterial obstruction (CT obstruction index-CTOI) determined with scoring system on spiral CT angiograms(SCTA). Material and methods. In 41pts (16 men, 25 women; age range 20-89 years, mean 65 years) with SCTA proven acute PE, plain chest films were retrospectively reviewed for signs of acute PE. A scoring system based on siteand degree of arterial obstruction enabled measurement of severity of obstruction on SCT angiograms. Some clinical signs (sudden onset dispnea, chest pain, syncope), ECG, pH and pCO2 of arterial blood were evaluated and compared between group with major PE (10 pts with CTOI>40%) and the rest (31 pts with CTOI40% (60%vs.22.5%;p value<0.05). There was no difference in frequency of clinical signs, pH and pCO2 of arterial blood between patients with major and minor PE. Conclusions. In pts with CT proven acute PE, oligemia on chest x-ray and ECG signs of rightventricular strain correlate with severity of pulmonary arterial obstruction. Clinical simptoms, pH and pCO2 of arterial blood show no correlation with degree of pulmonary arterial obstruction.
Keywords: diagnostika; Electrocardiography; Elektrokardiografija; Pljučna arterija; Pljučna embolija; Pulmonary Artery; Pulmonary Embolism; Radiography; rentgenska diagnostika; Thoracic Radiography; Tomografija radiografska, računalniška; Tomography, X-Ray Computed